DETERMINATIONOF REACTION KINETICS USING ONLINE X-RAY DIFFRACTION - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT X-ray diffraction (XRD) is a powerful technique for the study of polymorphism and polymorphic phase transformations.Monitoring of phase transformationdirectly has been ve/}' limited to-date. TheXRD system used in this study was used to determine the rate of transformationof pure glutamic acid a form to 13form in a solution mediatedphase. On eve/}' run starting from the pure a form, the transformationprocess was monitored continuously at fixed temperature, and separate experiments were performed as a function of temperature. The operating temperaturewas varied from 36 to 57 °C with 10%w/w solid concentration.Data were taken eve/}' 200 secondsuntil the transformationwas completed. Thispaper is concemed with a study of the transformationof the alpha (a) form of L-glutamic acid (L-GA) to the beta (13)form in order to determine the kinetic reaction. The rate constant (k), activation energy (Ea) and pre-exponential factor (A) were obtained. Sensitivity tests were also carried out to examineminimum detection limit whenboth a and 13present in the mixture. In addition, effect of particle size on XRD pattems was also determined. The results show that XRD gives useful information to observe polymorphism for pharmaceuticalmdust/}'. Keywords: XRD, polymorphism, glutamic acid, reaction kinetics